Circulating serum matrix metalloproteinase-3 and metalloproteinase-9 are not associated with echocardiographic parameters of diastolic function in asymptomatic type 2 diabetic patients - Zákovičová, E; Charvat, J; Kukacka, J; Chlumsky, J; Svab, P; Kvapil, M (The Journal of international medical research, 2010)
Serum concentrations of matrix metalloproteinase (MMP) 3 and MMP9 were evaluated in 82 asymptomatic type 2 diabetes mellitus patients without cardiovascular complications and in 41 non-diabetic control subjects. In the asymptomatic diabetic patients, the correlations of these concentrations with diabetes duration, selected biochemical parameters such as glycated haemoglobin (HbA(1c)), and echocardiographic parameters of diastolic function were also assessed. Pulsed and tissue Doppler echocardiography was performed in the two groups. Mean ± SD age was 61 ± 6 years for the asymptomatic diabetic patients and 61 ± 5 years for controls. Mean ± SD concentrations of MMP3 and MMP9 were significantly higher in the asymptomatic diabetic patients (67.5 ± 10.4 and 77.8 ± 28.8 μg/l, respectively) than in controls (47.2 ± 6.1 and 51.1 ± 13.7 μg/l, respectively). In the asymptomatic diabetic patients, MMP3 correlated only with albuminuria (r = 0.341) and MMP9 only with HbA(1c) (r = 0.262); neither MMP was correlated with echocardiographic parameters of diastolic function. Thus, in asymptomatic type 2 diabetic patients without cardiovascular complications, serum MMP3 and MMP9 were elevated, MMP9 was associated with HbA(1c) and MMP3 was associated with albuminuria, however, MMP3 and MMP9 were not associated with echocardiographic parameters of diastolic function.
Keywords: matrixová metaloproteinasa 3; kardiovaskulární nemoci; Humans; Case-Control Studies; hypolipidemika; lidé středního věku; echokardiografie; studie případů a kontrol; Echocardiography; diastola; Female; Antihypertensive Agents; lidé; Diabetes Mellitus, Type 2; Matrix Metalloproteinase 3; ženské pohlaví; Cardiovascular Diseases; Matrix Metalloproteinase 9; Male; Middle Aged; matrixová metaloproteinasa 9; Diastole; Hypolipidemic Agents; antihypertenziva; mužské pohlaví; diabetes mellitus 2. typu